Structural Equation Modeling Analysis of Critical, Creative, and Metacognitive Thinking Skills as Predictors of Reflective Thinking in Science Problem Solving - Diki Rukmana; Andi Suhandi; Achmad Samsudin (International Journal of Engineering, Science and Information Technology, 2026)
This study aims to model the relationships between critical, creative, and metacognitive thinking skills in shaping reflective thinking abilities among prospective science teachers, particularly within the context of solving complex science problems. A quantitative research approach was employed using Structural Equation Modeling (SEM), with data analysis conducted through SmartPLS software. The sample consisted of 162 students enrolled in science education courses during the odd semester of the 2024/2025 academic year. Data were collected using a standardized questionnaire that had undergone systematic content validity and reliability testing to ensure measurement accuracy and consistency. The measurement model analysis demonstrated that all indicators satisfied established validity and reliability criteria, with factor loading values exceeding 0.70 and Average Variance Extracted (AVE) values above 0.50. Furthermore, the structural model analysis revealed that critical thinking skills exerted the strongest positive and significant influence on reflective thinking abilities (? = 0.401; p 0.001), followed by metacognitive skills (? = 0.337; p 0.001) and creative thinking skills (? = 0.178; p 0.05). The coefficient of determination (R² = 0.716) indicates that the proposed model explains 71.6% of the variance in reflective thinking ability, demonstrating substantial explanatory power. These findings confirm that reflective thinking develops through the synergistic interaction of multiple higher-order thinking competencies rather than through isolated cognitive processes. Critical thinking supports systematic evaluation of evidence and reasoning, metacognitive skills facilitate awareness and regulation of cognitive strategies, while creative thinking encourages flexible exploration of alternative solutions. This study contributes to the advancement of theoretical frameworks in science teacher education and provides practical implications for designing instructional strategies, problem-based learning activities, reflective assessments, and teacher preparation programs that systematically integrate critical, creative, and metacognitive competencies to strengthen prospective science teachers’ reflective thinking and professional decision-making capabilities